Improvement of D-lactic acid production from methanol by metabolically engineered Komagataella phaffii via ultra-violet mutagenesis - Yoshifumi Inoue; Kaito Nakamura; Ryosuke Yamada; Takuya Matsumoto; Hiroyasu Ogino (Metabolic Engineering Communications)
Methanol has attracted attention as an alternative carbon source to petroleum. Komagataella phaffii, a methanol-assimilating yeast, is a useful host for the chemical production from methanol. A previous study successfully constructed a metabolically engineered K. phaffii GS115/S8/Z3 strain capable of producing D-lactic acid from methanol. In this study, we aimed to develop a strain with improved D-lactic acid production by applying ultra-violet mutagenesis to the D-lactic acid-producing strain, GS115/S8/Z3. The resulting mutant strain DLac_Mut2_221 produced 5.38 g/L of D-lactic acid from methanol, a 1.52-fold increase compared to the parent strain GS115/S8/Z3. The transcriptome analysis of the mutant DLac_Mut2_221 identified 158 differentially expressed genes, providing insights into key mechanisms contributing to enhanced D-lactic acid production. Metabolic engineering strategies for K. phaffii based on the knowledge gained from this study will contribute to improving the productivity of various useful chemicals from methanol.